Volleyball landings may explain ACL gender gap - Tillman, M. D.; Hass, C. J.; Brunt, D. (2002)
The sport of volleyball has grown continuously in popularity since its inception in 1895. Indeed, volleyball has become one of the most popular participant sports worldwide with more than 200 million competitors,1,2 a number comparable to the number of soccer participants reported by the Federation Internationale de Football Association.3 An indication of the worldwide popularity of all forms of volleyball is the acceptance of beach volleyball as an Olympic sport in 1996. Potential reasons for this popularity are that the sport requires a minimal amount of equipment, enthusiasts can participate throughout their lives, and participants can compete at a variety of skill levels. Women and girls, in particular, have shown increasing interest in and support for volleyball in the U.S. The National Collegiate Athletic Association reports that universities and colleges in the U.S. currently sponsor 975 women's teams. In addition, volleyball is the third most popular sport among high school girls in the U.S. with almost 400,000 players participating each year (as reported by the National Federation of State High School Associations). Rising injury incidence The rising interest in volleyball has been accompanied by a growing concern in the sports medicine community regarding the increased incidence of injuries.4 Surprisingly, the incidence of injury in volleyball is similar to the rates reported for other, more contact-based sports. Aagaard, Scavenius, and Jorgensen reported that the incidence of injury in volleyball is nearly equivalent to those observed in ice hockey and soccer.2 The risk of injury in volleyball is inherent in its dynamic and ballistic nature and the propulsion of the ball at speeds that can reach 145 km/h (90 mph).1 Participation in the sport at an elite level requires mastery of many physical skills and performance often depends on an individual's ability to propel him- or herself into the air during both offensive and defensive maneuvers. To perform a jump serve or a spike, the player jumps high into the air and strikes the ball at the highest point of the jump in an effort to propel the ball rapidly down on the opposing side of the net. Front-row players defend against spikes by jumping into the air with their hands raised to impede offensive attack. It is important to remember that spikes and blocks include not only jumps, but also landings, during which the kinetic energy generated in the jump is dissipated. Newtonian mechanics dictate that increases in jump height are accompanied by a proportional increase in kinetic energy that must be properly absorbed to avoid injury.5 These ballistic landings often result in ground reaction forces on the order of five times body weight.6 For a front-row specialist, who may jump 150 times during a regulation match, the deleterious effects of these forces are compounded alarmingly.7 Epidemiology The mechanisms and frequency of injuries in volleyball are intriguing and have been well studied. The jump-landing sequence is the most common source of injury.1 In fact, blocking and spiking are associated with more than 70% of volleyball injuries.8 More specifically, it is the landing techniques used in volleyball that may be related to lower extremity energy absorption and injury.5 The vast majority (90%) of volleyball injuries occur in the lower extremity with the knee joint being especially vulnerable.9 Injuries to the knee are of particular importance because they are associated with more lost time from sports participation than other injury sites.10 Perhaps the most serious knee injury is rupture of the anterior cruciate ligament. The hypothesis that women have a greater risk of ACL injury in volleyball than men1 is supported by the sports medicine literature, which indicates that women are more likely than their male counterparts to suffer ACL injuries during jumping and cutting sports. Comparisons of noncontact injuries suffered by athletes of different genders have confirmed that female athletes suffer ACL injuries more often than their male counterparts given the same sport and playing conditions.11 A noncontact injury is one in which the athlete does not collide with another athlete or any structure other than the ground. Arendt and Dick reported that female collegiate soccer players were more than twice as likely to sustain an ACL injury as male collegiate players, and female collegiate basketball players were four times as likely to sustain an ACL injury as male collegiate players.11 Malone and colleagues reported that female collegiate basketball players were eight times more likely to suffer an ACL injury than their male counterparts.12 Data from the NCAA Injury Surveillance System supported these findings.13 The theories proposed to explain the discrepancy between rates of ACL injury for men and women are based on anatomical and physiological elements believed to influence knee mechanics. These elements are typically divided into extrinsic and intrinsic factors. Extrinsic factors include muscular strength, level of conditioning, shoes, and motivation.14 Intrinsic factors include joint laxity, limb alignment, intercondylar notch size and shape, ligament size, and hormonal influences.14 Extrinsic factors can be controlled or influenced directly by the individual, while intrinsic factors are anatomical and physiological variations and are not directly controllable. Despite extensive research, no strong relationship between any single contributing factor and ACL injuries has been established. Perhaps more research regarding extrinsic factors such as jumping and landing techniques should be considered. Jumping and landing techniques Jumping and landing movements are integral features of many sports and have received considerable research attention with regard to ACL injury. Previous research on landing has concentrated on implications of the impact and resulting loads placed on the body, as well as the injury potential of various landing methods. For example, Kovacs et al is indicated that the landing strategy used by an athlete (forefoot versus heel-toe landing) has significant implications regarding the forces transmitted to the body and the body's ability to dissipate those forces.15 The jumping and landing techniques utilized by volleyball players may influence the likelihood of injury during the jump-landing sequence. Stacoff and colleagues analyzed the volleyball block jump in adult male athletes and found an initial vertical impact peak of between 1000 N and 2000 N at forefoot touchdown.16 Heel strike followed with an impact peak ranging from 1000 N to 6500 N. The height of the jump and the subsequent touchdown velocity were less important, however, than knee angle in predicting the magnitude of the GRF. Increased knee extension produced a greater impact on landing. Other researchers have found that vertical impact forces increase with the height of the jump as well as with knee extension angle.17,18 McNitt-Gray found that greater landing velocities produced greater knee extensor moments, suggesting that the quadriceps acted as shock absorbers.19 It has been hypothesized that the high number of jumps and the likelihood of a player losing his or her balance due to deviations in jumping technique are the primary causes of injury in volleyball.20 Little evidence exists, however, regarding jumping and landing technique preferences for female volleyball players. A recent analysis of elite female collegiate volleyball players provides some insight into the most frequently used jumping and landing techniques.7 The majority (86.5%) of offensive jumps were performed using a two-footed takeoff. Similarly, in more than 98% of defensive jumps, participants used both feet to propel themselves into the air. Landing frequencies did not follow this pattern. Half of the landings from spiking maneuvers were performed with two feet. The remaining 50% involved asymmetric foot contact: nearly 39% involved a left-foot-first landing and 11% used a right-foot-first technique. Less than half (47%) of landings following defensive blocks occurred on both feet, while 36% took place with the right foot first and almost 17% with the left. Nearly all offensive and defensive jumps performed by elite female volleyball players are executed using both feet.7 Jumping with both feet affords the athlete a wide and stable base of support for force production and maximal vertical leap height. Accordingly, very few injuries occur during the jump phase of blocks or spikes. On the other hand, nearly half of all landings in volleyball occur on only one foot. The most frequent mechanism of knee injury in volleyball (for both men and women) is an asymmetric landing from a jump.20 Female players' relatively high number of asymmetric landings could lead to a loss of balance and help to explain the increased incidence of injury in women. However, published data relative to jumping and landing techniques for men don't allow a direct comparison. Schafle stated that an occasional asymmetric landing increases the likelihood of knee ligament derangement.4 Mechanically speaking, these asymmetric landings jeopardize the landing limb because the energy created by both legs during the jump phase must be dissipated by a single leg during the landing. This circumstance may lead to the high-risk lower extremity alignment referred to as the "position of no return,"21 which is characterized by a forward-flexed and rotated back, adducted and internally rotated hip, valgus-positioned and flexed knee, external tibial rotation, and lack of control of the opposite foot. In this position, the muscles that would normally help the athlete remain erect cannot function properly because they are working at a mechanical disadvantage, which leads to a greater predisposition for injury.21 Injury prevention Preventing knee injuries is difficult in volleyball because it is an inherently high-risk sport. Schafle has suggested a rule change that would prohibit any contact with the center line.4 This change, though unlikely, might help reduce the incidence of ankle sprains, but would have little influence on the rate of knee injuries because most ACL injuries are noncontact. Strengthening the entire lower extremity is another possibility and would allow jumpers to dissipate the energy of landing through the muscles instead of the bones and ligaments.4 Another preventive suggestion, proposed by Briner and Kacmar, focuses on landing techniques.1 These authors suggested educating athletes about the importance of landing techniques and the significance of landing with slightly flexed knees and plantar-flexed feet. Such positioning at contact would provide a large range of motion over which the ground reaction forces could be dissipated. This coincides with the work of Zhang, Bates, and Dufek, who reported that the knee-joint extensors and plantar-flexors function as the primary energy dissipaters during landing.22 Physical training (in both strength and technique) may be the most practical and effective way of preventing injuries related to landing from a jump. The positive effects of training have been reported by Hewett et al.23 In their study, female athletes participated in plyometric jump training for six weeks. After training, maximum landing forces during a block were reduced by 22%, and adduction and abduction moments were decreased by 50%. These improvements could prevent athletes from reaching the "position of no return" and thereby decrease the incidence of injury in this population. Interestingly, no change in vertical leap performance was detected after training. Thus, it appears that training can reduce the likelihood of injury without affecting performance. Athletes who regularly engage in jump-landing sequences and are exposed to the consequent large impact forces should concentrate on performing landings using a toe-heel contact pattern with greater knee flexion whenever possible and practical.17 Although this technique requires greater muscular strength, it may help reduce the likelihood of injury. This can present strategic difficulties, however, because landing with a more flexed knee may prevent the player from executing his or her next move in a timely manner. Researchers, physicians, therapists, trainers, coaches, and athletes should focus on factors that are controllable in an effort to reduce injuries in volleyball. The most promising possibilities appear to be increasing strength, improving conditioning, and modifying jump-landing techniques. Source: BioMechanics